Pengaruh Kualitas Sistem dan kualitas Layanan Terhadap Kepuasan Serta Loyalitas Pelanggan Pengguna Listrik Prabayar dan Pascabayar - Wijayanti, Diah (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2019)
Abstract-The progress of a nation can be measured by today's large - size electric energy consumption per capita of concerned citizens . For the citizens of our country Indonesia , electricity is still a luxury item including commodities , proved still the majority of the people / citizens we have not been able to reach them . PLN give service as State power is not maximized . One of the breakthroughs that made PLN is electrical energy sales system Pre-paid and Post-paid , with hope for the people can choose one among the offered payment systems , to be able to choose where to do austerity . Satisfaction and customer loyalty is the most important factor in business competition . The three variables that will be used in this study is the quality system , quality of information , and quality systems . These factors might impact on satisfaction and customer loyalty . The proposed hypothesis is useful to examine the relationship three variables that influence customer satisfaction and loyalty . The method used is a sample of questionnaires with 200 residential electricity customers in Cikarang baru.Analisa data is performed with the approach of the Structural Equation Model ( SEM ) with AMOS 8.0 program . SEM analysis of the results shows that the model does not fit . Therefore modification of the model to test the hypothesis . Based on the results of data analysis has been conducted quality system found no significant influence on customer satisfaction and loyalty . While the other two variables , namely the quality of information and quality of services significantly influence customer satisfaction and loyalty . customer satisfaction and customer loyalty has no effect onelectricity.   . Keywords : Prepaid and Postpaid , influence , loyalty and customer satisfaction